Fresno County Bar Association's Witkin Luncheon with Keynote Speaker Bernard Witkin - Watkins, Howard::::::::: (1982)
John McGregor holding up framed photograph of Justice George Hopper Judge Annette LaRue at Fresno Hilton lectern